2014
DOI: 10.1007/s00420-014-0965-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ischemic heart disease following occupational exposure to welding fumes: a systematic review with meta-analysis

Abstract: Several studies indicate that welding is associated with a moderately increased risk of IHD; however, bias and confounding cannot be ruled out with reasonable confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It is known that WFs can cause also nonmalignant lung diseases. Additionally, occupational exposure to particle and WFs has been associated with an increased risk of cardiovascular disease, and fine particles (aerodynamic diameter < 2.5 micrometer µm) seem to play a key role [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that WFs can cause also nonmalignant lung diseases. Additionally, occupational exposure to particle and WFs has been associated with an increased risk of cardiovascular disease, and fine particles (aerodynamic diameter < 2.5 micrometer µm) seem to play a key role [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggested an association between welding fumes and increased risk of CVD [ 6 , 11 , 12 ]; for example, the standardized incidence ratio for acute myocardial infarction was 1.12 (95% CI 1.01–1.24) in a Danish prospective study of welders followed until 2006 [ 12 ] and the standardized mortality ratio for ischemic heart disease was 1.35 (95% CI 1.1–1.6) in a Swedish study of welders followed until 1995 [ 6 ]. However, one meta-analysis revealed that the relationship between welding fumes and CVD was not robust, since bias and confounding effects could not be ruled out [ 13 ]. Therefore, the association between occupational exposure to welding fumes and elevated CVD risk was not well established, despite of the general consensus that exposure to PM increases the risk for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study measurements of respirable dust and sampling of blood were not conducted on the same day, which may have affected the results. Welders have in earlier studies been associated with having increased risks of cardiovascular diseases, such as ischemic heart disease (Mocevic et al 2015 ) and increased blood pressure (Li et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%